2015
DOI: 10.1002/ejhf.243
|View full text |Cite
|
Sign up to set email alerts
|

The liver X receptor agonist AZ876 protects against pathological cardiac hypertrophy and fibrosis without lipogenic side effects

Abstract: Aims Liver X receptors (LXRs) transcriptionally regulate inflammation, metabolism, and immunity. Synthetic LXR agonists have been evaluated for their efficacy in the cardiovascular system; however, they elicit prolipogenic side effects which substantially limit their therapeutic use. AZ876 is a novel high‐affinity LXR agonist. Herein, we aimed to determine the cardioprotective potential of LXR activation with AZ876. Methods and results Cardiac hypertrophy was induced in C57Bl6/J mice via transverse aortic cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
0
28
0
5
Order By: Relevance
“…Cannon et al . also reported that an LXR-α agonist significantly improves transverse aortic constriction-induced cardiac dysfunction and cardiac fibrosis in vivo 29. Furthermore, Ang II and Ang(1-7), two important elements of the RAS, inhibit and activate LXR-α expression, respectively3031.…”
Section: Discussionmentioning
confidence: 95%
“…Cannon et al . also reported that an LXR-α agonist significantly improves transverse aortic constriction-induced cardiac dysfunction and cardiac fibrosis in vivo 29. Furthermore, Ang II and Ang(1-7), two important elements of the RAS, inhibit and activate LXR-α expression, respectively3031.…”
Section: Discussionmentioning
confidence: 95%
“…Although multiple mouse models for cardiac disease are available in this study, the mdx and TAC model were chosen because the origin and development of fibrosis in these two models is different. Secondly, both mouse models are frequently described in literature and often used to test anti-fibrotic therapies [1216]. The mdx mouse was chosen as a model of genetic cardiac disease [17, 18], while a mouse model with transverse aortic constriction (TAC) was chosen to represent acquired heart disease [19].…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, LXRs have been shown to attenuate hypertrophy in neonatal cardiomyocyte via improved metabolic substrate use, downregulation of collagen synthesis, and profibrotic gene expression in cardiac fibroblasts55; and they have reduced apoptosis by inhibition of caspase‐3 protein expression 56. Analysis of the gene profiling data revealed that the expression of cholesterol 7α‐hydroxylase ( Cyp7a ), a target gene activated by LxRα,57 was significantly increased by 3.3‐fold in INSL6‐treated mouse hearts compared with nontreated mouse hearts subjected to isoproterenol insult.…”
Section: Discussionmentioning
confidence: 99%